2011
DOI: 10.1007/s00520-011-1321-7
|View full text |Cite
|
Sign up to set email alerts
|

A dietitian-led clinic for patients receiving (chemo)radiotherapy for head and neck cancer

Abstract: A dietitian-led head and neck cancer clinic is associated with improved efficiency and nutritional management of head and neck cancer patients and offers a feasible model of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 19 publications
(16 reference statements)
2
35
0
Order By: Relevance
“…Wermker et al developed two prediction models with a prognostic accuracy of 90 % [46]. Kiss et al recently reported on a dietitian-led clinic for head and neck cancer patients undergoing (chemo)radiotherapy [47]. Outcomes included increased first contact for high-risk patients, significantly decreased nutrition-related hospital admissions, improved transition back to oral diets, and reduced unplanned insertions for tube feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wermker et al developed two prediction models with a prognostic accuracy of 90 % [46]. Kiss et al recently reported on a dietitian-led clinic for head and neck cancer patients undergoing (chemo)radiotherapy [47]. Outcomes included increased first contact for high-risk patients, significantly decreased nutrition-related hospital admissions, improved transition back to oral diets, and reduced unplanned insertions for tube feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes included increased first contact for high-risk patients, significantly decreased nutrition-related hospital admissions, improved transition back to oral diets, and reduced unplanned insertions for tube feeding. Overall, patient acceptance was high, quality of care was improved, and a substantial cost savings was realized [47]. …”
Section: Discussionmentioning
confidence: 99%
“…These results support previous research, which has shown that PEG duration may not be entirely related to dysphagia frequency/severity [50,112]. PEG duration and long-term PEG dependence may also be associated with a number of other factors, including race [95], performance status scores (i.e., Zubrod) [95], age [87], gender [85,87], tumor stage/cancer severity [87,95,118,119], cancer site [85,120], smoking status [118,120], the presence/absence of pre-treatment dysphagia [118,119], and the level of support offered to patients when transitioning from tube to oral feeding [121,122]. Therefore, using PEG dependence/duration as a marker of dysphagia has its drawbacks and may not accurately reflect a patient's swallow physiology or function.…”
Section: Peg Dependence/durationmentioning
confidence: 99%
“…Two recommend high risk patients receive a proPEG (Brown et al, 2013b;Wood, 2005). The third classifies patients as high or low nutritional risk, but favours a reactive approach to tube placement (Kiss et al, 2012).…”
Section: Guidelines For High Risk Patientsmentioning
confidence: 99%
“…All three sets of guidelines demonstrated significant clinical benefits following implementation such as less weight loss, fewer hospital admissions, reduced length of stay, fewer unplanned nasogastric tube (NGT) insertions, improved transition to oral diet posttreatment and reduced oncologist review at two weeks post-treatment (Brown, Ross, Jones, Hughes, & Banks, 2014a;Hughes et al, 2013;Kiss et al, 2012;Wood, 2005). The…”
Section: Guidelines For High Risk Patientsmentioning
confidence: 99%